Iyengar Yoga for Women: A Practising Tradition in the Making - Wittich, Agi (Religions of South Asia, 2018)
This article explores women-oriented Iyengar Yoga (IY) practices through a historical, textual and ethnographical analysis. These practices were inaugurated by the teachings of B. K. S. Iyengar and Geeta Iyengar and globally expanded by IY teachers. The research focuses on how these pioneering practices where formed, the way they are perceived with respect to the ancient yoga tradition, and the way they are implemented among IY teachers. Drawing on Iyengar literature and interviews with IY teachers, the article suggests that womenoriented practices are considered by Iyengar members as rooted in ancient knowledge which was illuminated by the Iyengars. Also, women-oriented IY practices manifest what might be considered as the distinct attributes of IY teachings. Women-oriented practices are perceived as a distinct, yet inseparable segment of IY practices. While Iyengar teachers express diverse standpoints regarding specialized practices’ necessity and usage, they are an inherent element of the contemporary Iyengar teaching tradition.